2012
DOI: 10.1007/s00114-012-0882-8
|View full text |Cite
|
Sign up to set email alerts
|

Dodo remains from an in situ context from Mare aux Songes, Mauritius

Abstract: Since 2005, excavations at Mare aux Songes, Mauritius, have revealed the presence of a very rich, ∼4,200-year-old fossil bone bed including dodo (Raphus cucullatus) bones and bone fragments. The recently excavated dodo assemblage comprises at least 17 individuals and is characterised by the presence of small and fragile skeletal elements, a dominance of leg elements and an absence of juveniles. The hydrology of the area suggests that dodos, like many other species, were probably lured to Mare aux Songes by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Both islands, together with Rodrigues, supported abundant giant tortoises when first visited by Europeans in the 17 th and early 18 th centuries, but thereafter the animals were exploited to extinction (Stoddart and Peake, 1979). The remains of giant tortoises were recovered in the 2006─2008 excavations at Mare aux Songes on Mauritius, described by Rijsdijk et al (2009) and Meijer et al (2012). Tortoise bones have also been recovered from caves on Rodrigues (Burney, 2011) but the species identity and age of these is not known.…”
Section: High Volcanic Islandsmentioning
confidence: 99%
“…Both islands, together with Rodrigues, supported abundant giant tortoises when first visited by Europeans in the 17 th and early 18 th centuries, but thereafter the animals were exploited to extinction (Stoddart and Peake, 1979). The remains of giant tortoises were recovered in the 2006─2008 excavations at Mare aux Songes on Mauritius, described by Rijsdijk et al (2009) and Meijer et al (2012). Tortoise bones have also been recovered from caves on Rodrigues (Burney, 2011) but the species identity and age of these is not known.…”
Section: High Volcanic Islandsmentioning
confidence: 99%
“…For example, data from the western part of the Indian Ocean indicate that around 4000 years ago the climate turned dryer, presumably as a result of a change in the monsoon domain (Gasse and Van Campo 1994;Marchant and Hooghiemstra 2004); El Niño events occurred more frequently after 5000 years BP (Shulmeister 1999), while between 4200 and 3800 cal years BP the frequency of El Niño events decreased strongly (Wanner et al 2008). Shulmeister and Lees (1995) recorded a marked decline in effective precipitation in Australia in the period considered, and Rijsdijk et al (2009) andMeijer et al (2012) tied the presence of a massive bone bed on Mauritius to this period of drought. Our data are in agreement with the existence of a quite rapid climate change around the Indian Ocean around 4 ka.…”
Section: Ecologymentioning
confidence: 90%
“…All previous osteological work was based upon unassociated, composite skeletons, combining bones from many individuals and both sexes. Therefore, precise reconstructions based on associated skeletal elements of the dodo's physique, locomotion, and physiology were not possible (Hume, 2005;Meijer et al, 2012;Hume et al, 2014a;Claessens et al, 2015a). In this memoir (Claessens et al, 2015b), we describe the osteology of two nearly complete, associated skeletons of the dodo that were collected around 1900 by French-born amateur naturalist Louis Etienne Thirioux in caves or, more likely, boulder scree in the valleys surrounding the mountains of central Mauritius (Hume, 2005;Claessens and Hume, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Paleoecological research has shown that the vertebrate mass mortality was triggered by a series of extreme climatic drought events that affected a large part of the southwestern Indian Ocean region (De Boer et al, 2014. A unique combination of local geomorphic and hydrotaphonomic factors, coupled with eustatic sea level rise, resulted in excellent preservation of the subfossil material, which provided data for interdisciplinary research on the taphonomy and ecology of the Mare aux Songes bonebed (Hume, 2005;Rijsdijk et al, 2009Rijsdijk et al, , 2011Meijer et al, 2012;Hume et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%